The Effect of Green Accounting, Carbon Emission Disclosure, and Green Innovation on Financial Sustainability - Lisa Veronika; Siti Kustinah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of green accounting, carbon emission disclosure, and green innovation on financial sustainability in 11 energy-sector companies listed on the Indonesia Stock Exchange during 2020–2024. Using quantitative methods and panel regression analysis, the results show that green accounting and carbon emission disclosure have no significant effect on financial sustainability, while green innovation has a significant positive effect. These findings indicate that environmental costs and disclosure practices have not yet contributed directly to financial outcomes, whereas innovation plays a more strategic role in enhancing long-term financial sustainability. This research provides empirical insights for companies and stakeholders regarding the importance of strengthening environmental innovation to support sustainable financial performance.